Faktor-Faktor yang Berhubungan dengan Kejadian Hipertensi di Kelurahan Kapuas Kanan Hulu Kecamatan Sintang Tahun 2023 - Akhmad Akhmad (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Hypertension is an increase in systolic blood pressure of more than 140 mmHg and systolic blood pressure of more than 90 mmHg on two measurements with an interval of five minutes in a state of sufficient or rest/calm. Based on visit data at the general poly at the Regional Technical Implementation Unit (UPTD) of Sungai Durian Health Center, namely in 2020 as many as 46cases, in 2021 as many as 54 cases and in 2023 as many as 32 cases with the highest cases every year in the Kapuas Kanan Hulu Village area as many as 24 cases. Objectives: In general, this study aims to determine the factors associated with the incidence of hypertension. Methods: This research is a quantitative research design using a cross-sectional approach, the population in this study is the community with an age range of 18-45 years as many as 5,022 with a sample of 58 respondents. Data analysis using chi square test. Results: there is a relationship between age (p value 0.040), gender (p value 0.022), history of hypertension (p value 0.006), attitude (p value 0.017), knowledge (p value 0.012), physical activity (p value 0.032), stress (p value 0.001) and smoking (p value 0.015) with the incidence of hypertension. Conclusion: There is a relationship between age, gender, history of hypertension, attitudes, knowledge, physical activity, stress and smoking with the incidence of hypertension.